SISTEM MANAJEMEN DAN VISUALISASI SYSLOG PERANGKAT JARINGAN KOMPUTER PADA ICT UNIVERSITAS DIPONEGORO BERBASIS ELK STACK - Fauzi, Adnan (Jurnal Sistem Komputer, 2020)
Abstract—Device monitoring is an important thing to manage networks. Information related network state or condition can be gathered through the device monitoring for administrators to make decisions regarding occurred events. Logs can be useful information to monitor network devices. Network administrator of Diponegoro University need a centralized log management system that can receive, manage, and analyze logs. This research identify functional requirements of log management system. Topology design and software that will be used by the log management system use DSR method. The next step is implementation of the topology, software, and application. The last step is testing the system and log management application. The results show that collecting centralized logs and processing these logs into information in the form of dashboards using ELK Stack application successfully implemented. The dashboard resulted by ELK Stack Application will be implemented on the web application using PHP programming language and Codeigniter framework. The test results show that system can receive logs and group the log according to the device location and the severity level of the log.